2016
DOI: 10.1038/ncomms13677
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radical-induced formation of highly oxidized organic compounds

Abstract: Explaining the formation of secondary organic aerosol is an intriguing question in atmospheric sciences because of its importance for Earth's radiation budget and the associated effects on health and ecosystems. A breakthrough was recently achieved in the understanding of secondary organic aerosol formation from ozone reactions of biogenic emissions by the rapid formation of highly oxidized multifunctional organic compounds via autoxidation. However, the important daytime hydroxyl radical reactions have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
399
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 231 publications
(472 citation statements)
references
References 47 publications
(92 reference statements)
33
399
1
Order By: Relevance
“…The selectivity of I − and NO − 3 toward more oxidized species as suggested here is consistent with the observations in previous studies (Lee et al, 2014;Berndt et al, 2016), which showed that these two reagent ions can have distinct sensitivities to the oxidized species having similar oxygen contents, depending on the identities and locations of the functional groups. It is clear in Fig.…”
Section: Mass Defect Plotssupporting
confidence: 92%
See 4 more Smart Citations
“…The selectivity of I − and NO − 3 toward more oxidized species as suggested here is consistent with the observations in previous studies (Lee et al, 2014;Berndt et al, 2016), which showed that these two reagent ions can have distinct sensitivities to the oxidized species having similar oxygen contents, depending on the identities and locations of the functional groups. It is clear in Fig.…”
Section: Mass Defect Plotssupporting
confidence: 92%
“…For example, previous studies using NO − 3 CIMS have reported a very low yield of HOMs from OH oxidation of monoterpene . However, a recent study using acetate CIMS found a significantly higher HOMs yields from the same system (Berndt et al, 2016). The reason for this difference is presumably a lower sensitivity of NO − 3 to HOMs formed in OH oxidation of monoterpene than that of acetate (Berndt et al, 2016).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations